Modelling the effect of intrinsic radiation damage on mechanical properties: The crystalline-to-amorphous transition in zircon. (May 2021) - Huber, Norbert; Beirau, Tobias
Abstract: Mechanical modelling using the level-cut Gaussian random field approach has been employed to simulate the effect of radiation induced amorphization on the Young´s modulus, Poisson´s ratio and hardness of zircon (ZrSiO4 ). A good agreement with previous nanoindentation experiments has been achieved. Two percolation transitions occur at ~16% and ~84% amorphous volume fraction, leading to deviations from linearity in the evolution of the Young´s modulus. Interface regions between crystalline and amorphous areas stabilise the hardness for a considerable amount of amorphous fraction. The modelling approach is promising for predicting the intrinsic radiation damage related evolution of the mechanical properties of various materials. Graphical abstract: Image, graphical abstract